Parental Involvement in Assisting the Student in the Social Domain: The Educators’ Perspective - Korem, Anat (Social Education Research, 2024)
Parental involvement is one of the key issues in education that remains a constant part of the public and academic agenda, but little is known about the perspective of educators on parental involvement in assisting the student in the social domain. It is essential to throw light on this perspective in order to construct an effective parent-educator partnership in this domain. This qualitative study focuses on educators’ perspectives (perceptions and strategies). It is based on analyses of 10 case studies perceived by educators as successful and 16 statements by educators, which were not connected to a specific case study, but expressed their views about parents generally. It was found that the educators’ perceptions include positive and negative aspects. Three types of effective strategies have emerged from the data: creating good communication with parents, giving practical advice to parents, and driving positive change in the relations between the child and their parents. The conclusions point to aspects that should be emphasized in teacher education, particularly professional training in how to develop social competence in students.